PEMANFAATAN SMART ROOM LITERASI BERBASIS INTERNET SEBAGAI UPAYA PENINGKATAN MOTIVASI BELAJAR SISWA PADA MASA PANDEMI COVID-19 - Ratri Wikaningtyas (CENDEKIA, 2021)
This research is motivated by the covid-19 pandemic which is bad for education.Education in Indonesia decided to do distance learning. There are many obstacles in the implementation of remote defense that cause students' learning motivation to decrease.Research is needed to improve students' learning motivation, one of which is the provision of smart room literacy.This study aims 1) Designing and creating more literacy smart rooms that can be used by underprivileged students.2) Helping to provide facilities and infrastructure during distance learning.3) Improving students' learning motivation during distance learning. This research uses qualitative approach. The method used in this research is qualitative descriptive.Then the research design used is survey research. Data collection techniques using interviews and questionnaires.The result of the interview outlines the constraints experienced by parents and students is the lack of knowledge of technological advances and the availability of learning facilities thus lowering the motivation of students' learning with an average percentage of 93%.The results of the questionnaire broadly stated that the use of smart room literacy increases students' learning motivation during distance learning.With an average satisfaction percentage of 95%.